The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1099/0022-1317-70-11-3043
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cowpea Mosaic Virus M RNA in Cowpea Protoplasts

Abstract: SUMMARYCowpea mosaic virus (CPMV) M RNA is translated in vitro into two polyproteins of Mr values 105000 (105K) and 95K. Using antiserum against the small capsid protein VP23, these proteins have now been detected in cowpea protoplasts, a few hours after inoculation with CPMV. These proteins could also be detected at later stages of infection, but only when proteolytic processing was inhibited by the addition of ZnCI> Using antiserum against a synthetic peptide, corresponding to a part of the overlapping C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
1
18
1
1
Order By: Relevance
“…Furthermore, the concentration of these products increased with the time of infection. This contrasts with the observation made with CPMV M-RNA-encoded polyprotein where the 105kDa/95 kDa species are detected only transiently (Rezelman et al, 1989). The observed increase in concentration of P38 precursor products observed can be attributed to either decreased proteolytic activity and/or to an excess of P2 synthesis versus processing capacity.…”
Section: P41fllcontrasting
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the concentration of these products increased with the time of infection. This contrasts with the observation made with CPMV M-RNA-encoded polyprotein where the 105kDa/95 kDa species are detected only transiently (Rezelman et al, 1989). The observed increase in concentration of P38 precursor products observed can be attributed to either decreased proteolytic activity and/or to an excess of P2 synthesis versus processing capacity.…”
Section: P41fllcontrasting
confidence: 96%
“…Many of the aforesaid proteins, some of which have been shown to be viral movement proteins, do not accumulate in vivo late in infection (Demangeat et al, 1992;Hibrand et al, 1992). In addition, CPMV 48K protein displays low stability and is almost completely degraded after 8 h of pulse-chase (Rezelman et al, 1989). Thus G F L V P38 protein behaved atypically in comparison to these proteins.…”
Section: Total Proteinsmentioning
confidence: 99%
“…It is therefore possible that the 58K and 48K proteins have different cellular locations and different functions. Evidence for this has been presented by Wellink et al (1987), Holness et al (1989) andRezelman et al (1989), who found that the 48K protein is present in both cytoplasmic and membrane fractions of protoplasts, whereas the 58K protein is found only in the cytoplasmic fraction. It is also interesting that the 48K protein is the only non-structural C P M V protein detectable in the culture medium (Wellink et al, 1987).…”
Section: Discussionmentioning
confidence: 85%
“…The regions encoding these proteins are located on the M RNA of the bipartite genome. This M RNA is translated into two overlapping polyproteins of 105K and 95K (Pelham, 1979;Vos et al, 1984;Rezelman et al, 1989), which are proteolytically processed to give the overlapping 58K and 48K nonstructural proteins and, via a 60K precursor, the 37K and 23K coat proteins . The B RNA encodes all the functions necessary for RNA replication (Goldbach et al, 1980;Eggen & van Kammen, 1988) and is able to replicate independently of the M RNA in cowpea protoplasts (Rezelman et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…1). Rezelman et aL (1989) showed recently that these proteins are also produced in CPMV-infected cowpea protoplasts.…”
mentioning
confidence: 99%